PENGARUH USIA DAN WAKTU PENGAMBILAN SAMPEL PADA SURVEILANS CAMPAK BERBASIS KASUS (CBMS) DI PULAU SUMATRA DAN DKI JAKARTA TAHUN 2009 - Mursinah, Mursinah; Jekti, Rabea Pangerti; Subangkit, Subangkit (Badan Penelitian dan Pengembangan Kesehatan, 2010)
Case-based measles surveillance (CBMS) in Indonesia began in Jogjakarta in 2008. In 2009 this surveillance expanded in seven province in Sumatera Island (South Sumatera, West Sumatera, Jambi, Bengkulu, Riau, Lampung, Bangka Belitung), DKI Jakarta, NTB and Gorontalo. Laboratory confirmation become important because many diseases had almost similar clinical appearance. The aim of this study is to determine age of the patients and time collecting samples which influence the positivity results. This research was a cross-sectional study using demographic data from CBMS cases in 2009 and serological confirmation results in National Measles Laboratory Jakarta. Out of 871 samples received, 31.3% were measles positive. 68.4% positive cases were from DKI Jakarta. Samples collected in 3 days after rash increased measles positive result 1.5 fold compared to those collected in 3-35 days (ORa= 1.48; 95% CI= 1.11-1.98, p value=0.000). Group with age under five years old increased measles positive result 5.75 fold compared to adult and old age group (ORa= 1.48; 95% CI = 3.61-9.21, p value= 0.006), meanwhile group with age 5-15 years increased measles positive result almost two fold (ORa= 1.97; 95% CI = 1.22-5.21, p value= 0.008). Age under five years and children until 15 years old and time collecting samples 3-35 days after rash were factors that increased measles positive results in CBMS 2009 in Indonesia. Key words: age under five years, time collecting specimens, measles, CBMS.